Hypertrophic Cardiomyopathy After a Single Dose of Dexamethasone in a Preterm Infant - Yusuf Kale; Ozge Aydemir; Ozben Ceylan; Ahmet Yagmur Bas; Nihal Demirel (Pediatrics and Neonatology)
Dexamethasone is widely used in preterm infants with severe pulmonary disease. Hypertrophic cardiomyopathy (HCM) is a transient side effect observed after multiple doses of dexamethasone. We report a preterm infant with myocardial hypertrophy after a single dose of dexamethasone (0.5 mg/kg) used to treat laryngeal edema secondary to prolonged intubation. A benign course was observed without left ventricular outflow tract obstruction and with recovery within 4 weeks. Myocardial effects of dexamethasone may be independent of dose and duration of treatment. The risk/benefit ratio must be carefully considered before using even a single dose of dexamethasone in preterm infants.